2019
DOI: 10.1080/10717544.2019.1609622
|View full text |Cite
|
Sign up to set email alerts
|

Proniosomal gel-derived niosomes: an approach to sustain and improve the ocular delivery of brimonidine tartrate; formulation, in-vitro characterization, and in-vivo pharmacodynamic study

Abstract: Brimonidine tartrate (BRT) is a hydrophilic a 2 adrenergic agonist used for the treatment of glaucoma. Glaucoma is an ocular disease affecting the anterior segment of the eye requiring lifetime treatment. Owing to the obstacles facing ocular delivery systems and hydrophilicity of BRT, frequent administration of the eye drops is required. Niosomes have been widely used to improve the ocular bioavailability of the topically applied drugs and to enhance the ocular residence time. However, they have drawbacks as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 64 publications
1
33
0
Order By: Relevance
“…These results are in accordance with Eldeeb et al [67] who studied the optimal conditions for the formulation of brimonidine tartrate-loaded proniosomes and found that the EE% of Span 60based proniosomes was higher than Tween 80-based ones. Figure 4 demonstrates that the Q12h of different Curcumin-loaded proniosomes ranged from 42.71 ± 1.74 to 94.91 ± 2.18%.…”
Section: The Effect Of Formulation Variables On Q 12h Of Curcumin-loasupporting
confidence: 91%
“…These results are in accordance with Eldeeb et al [67] who studied the optimal conditions for the formulation of brimonidine tartrate-loaded proniosomes and found that the EE% of Span 60based proniosomes was higher than Tween 80-based ones. Figure 4 demonstrates that the Q12h of different Curcumin-loaded proniosomes ranged from 42.71 ± 1.74 to 94.91 ± 2.18%.…”
Section: The Effect Of Formulation Variables On Q 12h Of Curcumin-loasupporting
confidence: 91%
“…Stirring was continued until the formation of gel base then left overnight for equilibration. Gel formulations were prepared by mixing the niosomal dispersions with the gels by a glass rod to have a final combination niosomes gel [27]. The prepared formulae were examined for their physical characteristics such as color, clarity, and homogeneity.…”
Section: Formulation Of Acetazolamide and Carvedilol Niosomes Gelmentioning
confidence: 99%
“…Glaucoma is considered as a neurodegenerative disease and often requires a lifetime treatment [ 55 , 110 , 111 ]. Glaucoma is an optic neuropathy that is characterized with retinal ganglion cell (RGC) death by apoptosis, resulting in degeneration of nerve axons and visual field defects [ 110 , 112 , 113 ].…”
Section: Niosome Based Treatment Strategies In Ocular Diseasesmentioning
confidence: 99%
“…The most prevalent factor associated with Primary Open Angle Glaucoma prognosis is the increased intraocular pressure (IOP) [ 110 , 113 , 114 ]. IOP rises because of the accumulation of aqueous humor in the anterior chamber, which might be due to the overproduction of fluid or the blockage of drainage system [ 55 ]. The elevated IOP causes an imbalance in the retinal blood flow, which leads to the degeneration of the optic nerve [ 55 ].…”
Section: Niosome Based Treatment Strategies In Ocular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation